Assessment of structural modification and time-dependent behavior of poly (lactic acid) based composites upon hydrolytic degradation. (5th March 2022) - Lv, Shanshan; Liu, Chen; Li, Han; Zhang, Yanhua
Graphic abstract: Highlights: Time-dependent hydrolysis behavior of PLA and starch/PLA composites were studied. Starch slightly slowed down the hydrolysis of PLA, but did not reduce the final hydrolytic degree. The autocatalysis effect was more prominent at a higher temperature. Abstract: Structural modification of starch/PLA composites caused by hydrolysis was evaluated at different temperatures. Water uptake of starch/PLA composites showed a time-dependent behavior which did not follow the Fickian behavior well. Molecular weight also showed a time dependence, especially at 50 °C. Combining water uptake and molecular weight change together, the entrapment of acidic products in the bulk could increase the hydrophilicity of materials and catalyze the hydrolysis. The chain scission occurred at the C = O in the PLA chains according to the FTIR results. The presence of starch may induce the hydrolysis to take place at the interface between starch and PLA matrix. In addition, starch may slow down the hydrolysis rate slightly without influencing the hydrolysis degree. This research should provide valuable information for designing green materials to be applied in water-present conditions.